"Is there no Balm in Gilead?": Health, Illness, Death, and Dying in the Hebrew Bible and Today. (July 2021) - Kaminsky, Joel S.
This essay argues that the Hebrew Bible contains conceptual resources that can contribute to and enrich the ongoing discussions surrounding healthcare in the U.S. and in other modern Western societies. These biblical ideas may help us reframe our understandings of sickness and health, something urgently needed if we wish individuals and their families to have less medically invasive and less alienating experiences of illness, most especially during end of life care.